O świecie analizowanym krokami w książkach obrazkowych dla dzieci - Jerzy Szyłak (Załącznik Kulturoznawczy)
Footpath Flowers is an example of a picture book for children whose main topic is the everyday. Numerous children’s authors tell stories about ordinary human existence. Many of them try to make this quotidian reality extraordinary. Most importantly, they make everyday events worth telling. In persuading readers to share their day-to-day experiences, they teach them to look for a meaning in what they do and deal with.